The acoustic oceanographic buoy telemetry system: an advanced sonobuoy that meets acoustic rapid environmental assessment requirements - Silva, A. (2014)
In the past few years Rapid Environmental Assessment (REA), applied to shallow waters, has become one of the most challenging topics in ocean acoustics. The REA concept evolved after the cold war when the outset of regional conflicts shifted the potential operational areas from open ocean towards littoral areas, and has been identified by NATO as a new warfare requirement.